Penggunaan Media Pembelajaran Berbasis Game Edukasi Kuis pada Mata Pelajaran Ekonomi untuk Meningkatkan Minat dan Hasil Belajar Siswa Kelas XI IPS 7 SMAN 6 Kediri: Penggunaan Media Pembelajaran Berbasis Game Edukasi Kuis pada Mata Pelajaran Ekonomi untuk Meningkatkan Minat dan Hasil Belajar Siswa Kelas XI IPS 7 SMAN 6 Kediri - Surya Ayu Azizah; Elis Irmayanti; Tjetjep Yusuf Afandi (CV. AFDIFAL MAJU BERKAH, 2025)
This research is motivated by students who often feel bored, bored and lack of interest in the learning process. The attention and concentration of students become unfocused so that students become lazy and do not do the tasks given by the teacher. The purpose of this study was to increase the interest and learning outcomes of students in class XI IPS 7 SMAN 6 Kediri Economic Subjects through learning media based on quizizz educational games. This research approach was carried out using the Classroom Action Learning (PTK) method. This research must be carried out in a planned manner and according to existing procedures. The implementation of this research through II cycles, where cycle I interest and expected learning outcomes are good but not yet maximized so it is necessary to hold cycle II to increase the interest and learning outcomes of students in class XI IPS 7 SMAN 6 Kediri. The use of quizizz educational game-based learning media in Economics subjects has increased, the data can be seen from the pre-cycle learning outcomes of 37% after applying quizizz learning media in cycle I learning outcomes increased by 79%, while in cycle II learning outcomes increased by 97%. Interest in learning in economic subjects also increased as evidenced by the results of observations of learning interest in cycle I reaching 70% and in cycle II experiencing an increase of 87%. This proves that learning media based on quizizz educational games can increase the interest and learning outcomes of students of class XI IPS 7 SMAN 6 Kediri.